Zinc-air cell with KOH-treated agar layer between electrode and electrolyte containing hydroponics gel - Othman, Raihan; Yahaya, Abdul Hamid; Arof, Abdul Kariem (Ecole Polytechnique de Montreal, 2002)
The capacity of zinc-air cell employing gelled KOH electrolyte has been enhanced markedly as thin KOH-treated gelatinized agar layer was applied between the electrode-gelled electrolyte interfaces. Depending on discharge load, the cell capacity showed an improvement ratio from 1.4 to 3.1. The agar layer improves the electrode-gelled electrolyte interfaces and simultaneously serves as the electrolyte reservoir to both electrodes. Preliminary study on porous zinc anode fabricated from dried zinc-graphite-gelatinous agar paste showed convincing result. A 1470-mAh zinc-air cell of monopolar design at 100.0 mA discharge load has been demonstrated.